Analisis Produktivitas pada Pengolahan Ikan Tuna Cube di PT. Aceh Lampulo Jaya Bahari - Akmal, Abdiel Khaleil; Ridha, Arrazy Elba; Hadi, Khairul (Jurnal Optimalisasi, 2024)
PT. Aceh Lampulo Jaya Bahari is a nautical product manufacturer based in the Lampulo fishing port, Banda Aceh, Indonesia. Productivity is a comparison of input and output that indicates how effectively resources are managed and exploited to obtain the best results. High production means there is less likelihood of delays. PT. Aceh Lampulo Jaya Bahari's productivity achievement indicator values fluctuate annually, with some years seeing low or high production.  The purpose of this study is to identify productivity-influencing elements, as well as to estimate the level of labor productivity, production amount, total productivity, and the difference in production amount when processing tuna cubes at PT. Aceh Lampulo Jaya Bahari. This study examines monthly production data from 2023 to determine worker productivity and output. The method is to measure partial and total productivity and then launch monthly productivity changes. The study's findings demonstrate that labor productivity and tuna cube output are higher than number one, indicating productive performance. PT. Aceh Lampulo Jaya Bahari met its production objective of 350 kg per month, with an average total labour productivity of 2.6%. This study advises that firms maintain production consistency and form a network of collaborating partners to ensure raw material availability.